Application performance on the Direct Access File System. - Fedorova, Alexandra (Software engineering notes.)
The Direct Access File System (DAFS) is a distributed file system built on top of direct-access transports (DAT). Direct-access transports are characterized by using remote direct memory access (RDMA) for data transfer and user-level networking. The motivation behind the DAT-enabled distributed file system architecture is the reduction of the CPU overhead on the I/O data path.We have created an implementation of DAFS for the FreeBSD platform. In this paper we describe the performance evaluation study of DAFS that we have performed using this software. The goal of this study is to determine whether the architecture of DAFS brings any fundamental performance benefits to applications compared to traditional distributed file systems, such as NFS. We perform comparison of DAFS to a version of NFS optimized to reduce the I/O overhead. In order to thoroughly understand the impact of DAFS on application performance, we consider a diverse range of applications workloads.We conclude that DAFS can accomplish superior performance for latency-sensitive applications, outperforming NFS by up to a factor of 2. Bandwidth-sensitive applications do equally well on both systems, unless they are CPU-intensive, in which case they perform better on DAFS. We also found that RDMA is a less restrictive mechanism to achieve copy avoidance than that used by the optimized NFS.